Prevalence, distribution and antimicrobial resistance profiles in poultry meat samples from India: a systematic review - Pooja Sajish, V.; Uzzaman, Nazim; Aramvalarthan, Niroshini; Asaduzzaman, Muhammad (Frontiers in Veterinary Science, 2025)
IntroductionChicken meat is a widely consumed source of protein in India but increasing reports of bacterial contamination and antimicrobial resistance (AMR) raise significant public health concerns. This systematic review aims to assess the prevalence of key bacterial pathogens in chicken meat across India and their resistance profiles.MethodsA comprehensive literature search was carried out across PubMed, Web of Science, and Scopus databases for studies published up to August 2024. Additionally, gray literature was retrieved using Google Scholar. Studies that identified bacterial isolates from chicken meat samples in India and reported antimicrobial susceptibility results were selected for inclusion. Data were extracted on bacterial species, sample location, antibiotics tested, and resistance rates using Microsoft Excel. A heatmap and summary tables were generated to visualize resistance trends.ResultsA total of 32 studies were included in this review, with Escherichia coli and Salmonella spp. emerging as the most frequently detected pathogens. High resistance rates were observed to ampicillin, tetracycline, ciprofloxacin, and streptomycin. The overall multidrug resistance (MDR) rate exceeded 60% for several species. Resistance genes such as bla, tet, and sul families were frequently reported, along with virulence genes like invA and icaA.ConclusionThe widespread presence of multidrug-resistant bacteria in Indian chicken meat underscores the urgent need for robust surveillance, regulatory action on antibiotic use in poultry, and adoption of a One Health approach to mitigate AMR transmission.